Iowa Birdline update, April 27, 1992 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1992)
Email for the Iowa Birdline update for April 27, 1992. Highlights of the update include sightings of Black Rails, a Eurasian Wigeon, Cinnamon Teal and Chestnut-collared Longspurs. Also included are handwritten notes for the next week's update with sightings of Clay-colored Sparrows in several locations and a Rose-breasted Grosbeak that was back in Iowa City. Epson - sheet feed/flatbed